PERAN PENDIDIKAN AGAMA ISLAM DALAM PEMBINAAN SPIRITUAL PASIEN PSIKOTIK SKIZOFRENIA - Moch Khafidz Fuad Raya (Research Department (Lemlit) Islamic Institute of Darullughah Wadda’wah Bangil, Pasuruan, 2020)
AbstractIslamic religious education is an effort to educate humans in accordance with the teachings of Islam as a guide for one's life. Islamic Religious Education in reality only focuses on education organized by educational institutions or institutions from elementary to tertiary levels, but it has not touched the empirical areas faced by society such as Schizophrenia. This article uses Library Research Design. The results of the study is the number of cases that occur due to psychotic disorders has made a number of mental hospitals implement the forms of activities with the nuances of Islamic Religious Education in dealing with schizophrenia psychotic patients, such as Islamic counseling therapy, Islamic adab, Miliu therapy, interacting politely and kindly, and Islamic studies. These forms of handling have proven that Islamic Religious Education actually covers areas of medicine and health sciences, which in reality many consider Islamic Religious Education cannot touch these areas. A more in-depth study of the role of Islamic Religious Education is needed in order to make a real contribution to the problems faced by society.Keywords: Islamic Religious Education, Schizophrenia, Spiritual Development. AbstrakPendidikan Agama Islam merupakan upaya mendidik manusia sesuai dengan ajaran agama Islam sebagai petunjuk dan pedoman hidup seseorang. Pendidikan Agama Islam pada kenyataannya hanya berkutat pada pendidikan yang diselenggarakan oleh institusi atau lembaga pendidikan dari jenjang dasar sampai perguruan tinggi, namun belum menyentuh wilayah-wilayah empirik yang dihadapi oleh masyarakat seperti Skizofrenia. Artikel ini menggunakan design penelitian kepustakaan. Hasil yang diperoleh yakni banyaknya kasus yang terjadi akibat gangguan psikotik ini membuat sejumlah rumah sakit jiwa menerapkan bentuk kegiatan yang bernuansa Pendidikan Agama Islam dalam menangani pasien psikotik skizofrenia, seperti Terapi konseling Islami, Adab Islami, Miliu terapi, berinteraksi dengan sopan dan ramah, serta Pengkajian Islami. Bentuk-bentuk penanganan tersebut telah membuktikan bahwa sebenarnya Pendidikan Agama Islam mencakup wilayah-wilayah kedokteran dan ilmu-ilmu kesehatan yang dalam kenyataannya banyak yang menilai Pendidikan Agama Islam tidak dapat menyentuh wilayah tersebut. Dibutuhkan kajian yang lebih mendalam mengenai peran Pendidikan Agama Islam agar dapat memberikan sumbangsih nyata pada problem-problem yang dihadapi oleh masyarakat. Kata Kunci: Pendidikan Agama Islam, Skizofrenia, Pembinaan Spiritual.